Thailand Economic Monitor, December 2012 - World Bank (Washington, DC, 2017)
The Thai economy in 2012 rebounded from the severe floods but continues to be affected by the slowdown in the global economy. Real GDP in 2012 is projected to grow by 4.7 percent supported by the rebound in household consumption and greater investments by both the private and public sectors as part of flood rehabilitation and the government s consumption-stimulating measures. The economy is projected to grow by 5 percent in 2013 as manufacturing production fully recovers and the global economy sees a modest recovery. Exports in 2013 are therefore expected to grow by 5.5 percent compared to only 3.6 percent in 2012. Budget deficit will be 2.5 percent of GDP for FY2013 plus additional off-budget spending for water resource management projects in FY2013. Public debt is estimated to be close to 50 percent of GDP in 2013. The paddy pledging scheme is estimated to cost around 3.5 percent of GDP each year, while the actual losses will be realized once the rice stocks are sold. The minimum wages have been raised by 40 percent nation-wide in 2012 and will be raised to a uniform rate of THB300 per day. Developing higher skills is imperative for higher incomes, living standards, and for Thailand to grow sustainably and inclusively. Thailand can do better in enabling the poor and vulnerable groups to participate in productive economic activities by pursuing a coordinated approach between universal and targeted social policy.